The synthesis, characterization, electrochemical and spectroelectrochemical properties of a novel, cationic, water-soluble Zn phthalocyanine with extended conjugation - KOCA, ATIF (ELSEVIER SCI LTD, 2011)
A novel Zn phthalocyanine substituted with four dimethylaminocinnamaldiminophenyloxy substituents at peripheral positions was obtained by the condensation of various 4'-aminophenoxy substituted phthalocyanines and 4-(dimethylamino)cinnamaldehyde Quaternization of the dimethylamino functionality produced cationic Zn phthalocyanines which were soluble in both water and other polar solvents such as methanol and DMSO The novel compounds were characterized using elemental analysis IR H-1 NMR UV-Vis and MALDI-TOF MS spectral data Electrochemical in situ spectroelectrochemical and in situ electrocolorimetric measurements revealed that the complexes undergo electron transfer reactions via the nitro and amine groups in addition to common Pc ring-based processes (C) 2010 Elsevier Ltd All rights reserved
Keywords: Phthalocyanine; Zinc; Schiff base; Quaternization; Spectroelectrochemistry; Extended conjugation; NONLINEAR-OPTICAL-PROPERTIES; METAL-CONTAINING PHTHALOCYANINES; IN-SITU; COMPLEXES; BEHAVIOR; METALLOPHTHALOCYANINES; DERIVATIVES; POLYMERS; BEARING; IODINE